Club foot, an adverse outcome of early amniocentesis: disruption or deformation?. Issue 11 (1st November 1999) - Farrell, S A; Summers, A M; Dallaire, L; Singer, J; Johnson, Jo-Ann M; Wilson, R D
Abstract : An association between the occurrence of club foot and early amniocentesis has been reported. The largest of these randomised studies was the Canadian Early and Mid-Trimester Amniocentesis Trial. Data describing the neonatal outcome, focusing on this association, are presented. Possible mechanisms for the association and the implications for the development of club foot are discussed.